Rethinking education in the age of technology : the digital revolution and schooling in America - Collins, Allan, 1937-; Halverson, Richard (New York : Teachers College Press, 2009)
In Rethinking Education in the Age of Technology, Allan Collins and Richard Halverson argue that the knowledge revolution has transformed our jobs, our homes, our lives, and therefore must also transform our schools. This groundbreaking book offers a vision for the future of American education that goes well beyond the walls of the classroom to include online social networks, distance learning with "anytime, anywhere" access, digital home schooling models, video-game learning environments, and more. --from publisher description.
How education is changing -- The technology enthusiasts' argument -- The technology skeptics' argument -- The development of American schooling -- The seeds of a new system of education -- The three eras of education -- What may be lost and what may be gained -- How schools can cope with the new technologies -- What does it all mean? -- Rethinking education in a technological world.
Includes bibliographical references and index.
Keywords: Education -- Effect of technological innovations on -- United States; Educational technology -- United States; Educational change -- United States; Technological innovations -- Social aspects -- United States; USA